Marital commitment in Filipino spouses: Adaptation and validation study of the Stanley and Markman's commitment inventory - Rapirap, Raquel Tan (Animo Repository, 2008)
The goal of this study was to adapt and to validate in the Filipino setting the Stanley and Markmans (1992) Commitment Inventory which includes the personal dedication scale and the constraints scale. Because extant literature showed personal satisfaction as an important contributory factor to commitment, a new researcher-constructed personal satisfaction subscale was added to the personal dedication scale. In addition, because organizational commitment was shown to work against commitment in marriage, the organizational commitment subscales of Meyer, Allen, and Smith (1993) were added to the constraints scale. The modified instruments were administered to 235 male and female employed married Filipinos. The personal dedication and constraint scales showed adequate overall reliability coefficient but individual subscales had less than adequate reliability. In terms of factor structure, all personal dedication subscales loaded on one factor, thus confirming the existence of a personal dedication scale. However, the constraints subscales loaded on different factors, with some loading on the personal dedication factor, suggesting that constraints did not form one factor. iii Marital Commitment in Filipino Spouses The criterion-related validity of the personal satisfaction scales was established through regression analyses with these scales predicting marital satisfaction, happiness, and quality over and above what the constraints subscales predict. On the other hand, the constraints subscales did not predict a substantially significant one of the variance of marital satisfaction, happiness, and quality over and above what personal satisfaction scales predicted. Finally, spouses with and without indications of instability did not differ so much in terms of constraints as in terms of personal dedication. Thus, marital commitment is defined not by the circumstances (constraints) that surrounded marriage but by personal dedication of respondent that defines the commitment to marriage.